Studi Komparasi Kelayakan Teknis dan Lingkungan Pemanfaatan Limbah B3 Sandblasting terhadap Limbah B3 Sandblasting dan Fly Ash sebagai Campuran Beton - Dermawan, Denny; Ashari, Mochammad Luqman (Universitas Diponegoro, 2018)
Fly ash and sandblasting slag widely used as concrete’s builder because it contains quite high silica (SiO2) approximately 58,20% and 98,97%. Fly ash and sandblasting slag can increase concrete power pressure and contains characteristic like cement. Method of concrete making and technical feasibility test on this research use SNI standar (SNI 03-2834-2000). Environmental feasibility test use Toxicity Characteristic Leaching Procedur (TCLP) according PP No. 101 tahun 2014. The results of this research show that the use of sandblasting slag can increase concrete power pressure at age of immersion 28 days. Concrete power pressure with 5%; 10%; 15%; and 20% sandblasting slag are 16,32 MPa; 17,81 MPa; 18,89 MPa; and 15,24 MPa. The use of sandblasting slag and fly ash can increase concrete power pressure at age of immersion 28 days. Concrete power pressure with 5% sandblasting slag and 30% fly ash; 10% sandblasting and 25% fly ash, 15% sandblasting and 20% fly ash, and 20% sandblasting and 15% fly ash are 18,53 Mpa, 16,08 MPa, 17,20 Mpa, and 15,91 MPa. Based on the TCLP test, the concentration of heavy metal substances in 10% SBE are below the standard. Thus, it is scientifically proven to conclude that concrete with 10% and 15% sandblasting slag and 5% sandblasting slag and 30% fly ash; 15% sandblasting and 20% fly ash are technically proper and safe for the environment.